Probing trace levels of prometryn solutions: from test samples in the lab toward real samples with tap water - Rubira, Rafael J. G. [UNESP]; Camacho, Sabrina A. [UNESP]; Aoki, Pedro H. B. [UNESP]; Paulovich, Fernando V.; Oliveira, Osvaldo N.; Constantino, Carlos J. L. [UNESP] (Springer Nature, 2016)
Growing food demand has been addressed by protecting crops from insects, weeds, and other organisms by increasing the application of pesticides, thus increasing the risk of environmental contamination. Many pesticides, such as the triazines, are poorly soluble in water and require trace detection methods, which are normally achieved with high-cost sophisticated chromatography techniques. Here, we combine surface-enhanced Raman scattering (SERS) with multidimensional projection techniques to detect the toxic herbicide prometryn in ultrapure, deionized, and tap waters. The SERS spectra for prometryn were recorded with good signal-to-noise ratio down to 5 × 10−12 mol/L in ultrapure water, approaching single-molecule levels, and 5 × 10−9 mol/L in tap water. The latter is one order of magnitude below the threshold allowed for drinking water. In addition to providing a fingerprint of prometryn molecules at low concentrations, SERS is advantageous compared to other methods since it does not require pretreatment or chemical separation. The multidimensional projection methods and the detection procedure with SERS are entirely generic, and may be extended to any other pesticide or water contaminants, thus allowing environmental control to be potentially low cost if portable Raman spectrophotometers are used.